Notebook 01 (July 1969-February 1970) - Hutchison, Alexander (1969)
Alexander ("Sandy") Hutchison (1943-2015) was a Scottish poet who taught at various colleges and universities on Vancouver Island between the 1960s-80s, including the Department of English at the University of Victoria in 1966. These notebooks contain content ranging from notes about/from various philosophers, to personal correspondence, to drafts of his poetry.